1998
DOI: 10.1159/000020862
|View full text |Cite
|
Sign up to set email alerts
|

Massive Intracranial Immature Teratoma with Extracranial Extension into Oral Cavity, Nose, and Neck

Abstract: We present a case of congenital massive intracranial teratoma with extracranial extension into oral cavity, nose, and neck diagnosed by antenatal ultrasonography at 25 weeks of gestation. The fetus was delivered by cesarean section because of massive fetal head size and severe maternal pregnancy-induced hypertension. At necropsy the tumor was found to be an immature teratoma, with no recognizable normal brain tissue. An additional finding was hepatomegaly secondary to extensive extramedullary hematopoiesis. Ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Rupture of the extremely thin skull has been reported several times [4][5][6][7][8][9] . Nonetheless, several authors have used encephalocentesis to avoid cesareans [3,9,17]. In our case, a caesarean appeared inappropriate for several reasons: in view of the fetal death we preferred to avoid creating a uterine scar, …”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Rupture of the extremely thin skull has been reported several times [4][5][6][7][8][9] . Nonetheless, several authors have used encephalocentesis to avoid cesareans [3,9,17]. In our case, a caesarean appeared inappropriate for several reasons: in view of the fetal death we preferred to avoid creating a uterine scar, …”
Section: Discussionmentioning
confidence: 84%
“…Of brain tumors present at birth, 29-50% are teratomas [2] . Three principal forms are described: a major form, as here, which entirely replaces normal cerebral anatomic structures, a much smaller teratoma that is complicated by hydrocephaly, and a form with extracerebral extension to any combination of the eye socket, mouth, nose, and neck [3] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal analyses were performed in 17 cases, most of them after amniocentesis [7]. Only 3 of these teratomas had a pathologic karyotype affecting both fetus and tumour [3,11,16], while in 5 studies a normal diploid karyotype was found in fetus and tumour [1,5,12,13,17]. In the remaining 9 cases karyotyping was performed on the fetus but not on tumour material [7].…”
Section: Discussionmentioning
confidence: 99%
“…They typically involve the midline structures such as pineal region, the hypothalamic area, quadrigeminal plate, and the suprasellar region. 2,7,17 In the case when the site of origin can be determined, the most common primary sites are the cerebral hemispheres, followed by the third ventricle and the pineal region. 18 The radiological appearance of teratomas depends on the contents of the tumor.…”
Section: Teratomasmentioning
confidence: 99%